Appreciating Analytic Philosophy A Conversation with Scott Soames. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Scott Soames, Distinguished Professor of Philosophy at University of Southern California. Scott Soames is specialized in the philosophy of language and the history of analytic philosophy. This detailed conversation provides a detailed introduction to analytic philosophy, including some examples of contemporary relevance to a wide range of other fields. This carefully-edited book includes an introduction,The Utility of Philosophy, and questions for discussion at the end of each chapter. Howard Burton was the Foundin.